2021
DOI: 10.1186/s12903-021-01876-7
|View full text |Cite
|
Sign up to set email alerts
|

First trimester exposure to ambient gaseous air pollutants and risk of orofacial clefts: a case–control study in Changsha, China

Abstract: Background A growing body of studies have investigated the association between air pollution exposure during early pregnancy and the risk of orofacial clefts, but these studies put more emphasis on particulate matter and reported inconsistent results, while research on the independent effects of gaseous air pollutants on orofacial clefts has been quite inadequate, especially in China. Methods A case–control study was conducted in Changsha, China fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Several studies recognized an increased incidence of CL/P after exposure to CO (carbon monoxide), NO 2 (nitrogen dioxide), and SO 2 (sulfur dioxide). CP cases were related only to NO 2 exposure [ 43 , 44 ]; no correlation was observed with O 3 (ozone) [ 43 , 45 ]. During the 5–10 gestational weeks, exposure to environmental particulate pollution with a diameter ≤ 2.5 μm (PM2.5) is correlated with a 43% increase in CP risk for each 10 μg/m 3 increase in PM2.5 concentrations [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies recognized an increased incidence of CL/P after exposure to CO (carbon monoxide), NO 2 (nitrogen dioxide), and SO 2 (sulfur dioxide). CP cases were related only to NO 2 exposure [ 43 , 44 ]; no correlation was observed with O 3 (ozone) [ 43 , 45 ]. During the 5–10 gestational weeks, exposure to environmental particulate pollution with a diameter ≤ 2.5 μm (PM2.5) is correlated with a 43% increase in CP risk for each 10 μg/m 3 increase in PM2.5 concentrations [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biological mechanism by which gaseous air pollutants can cause OFCs remains unclear. However, there are several hypotheses: hypoxia generated by CO; DNA methylation caused by NO 2 ; and oxidative stress caused by SO 2 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature on the association between SO 2 exposure during pregnancy and the risk of CL/P, Jiang W et al observed a signi cant positive correlation between SO 2 exposure during pregnancy and the risk of CL/P, with RR = 1.350, 95%CI=(1.140,1.610), and the remaining correlation was found in the remaining ve articles [23]. The combined RR = 1.111, 95%CI= (0.956,1.291) was not statistically signi cant.…”
Section: Association Between So 2 and Ofcsmentioning
confidence: 98%
“…After full-text reading, 53 articles that did not meet the requirements were excluded, including 22 articles on animal experiments, 28 articles on reviews, conferences, and case reports, and 3 articles on lack of data evaluation. Finally, 11 articles were included in the study [22][23][24][25][26][27][28][29][30][31][32]( Fig. 1).…”
Section: Literature Selectionmentioning
confidence: 99%